Do it yourself marketing research / George Edward Breen - Breen, George Edward (Estados Unidos de America: Kingsport Press, 1977)
What is do-it yourself marketing research?, evaluation of a problem, how to plan a study, how to use secondary sources, how to conduct a mail questionanire study, how to interview, group interviewing, special research for retallers, what you need to know about sampling, how to write a report that will get action, how to choose an outside research firm, if necessary, company politics how to get your research taken.
Contents, table, illustrated.
Col. Admón
Keywords: 1. RESEARCH-ANALYSIS-MARKET 2. MARKETING RESEARCH 3. MARKETING-RESEARCH 4. ECONOMY-RESEARCH 4. ADMINISTRATION-BUSINESS